A critical analysis of the cybersex phenomenon from the perspective of John Paul II's theology of the body - Hastuti H. Anak Ampun; Carolus Borromeus Mulyatno (CV. Literasi Indonesia, 2026)
The development of digital technology has fundamentally transformed the ontology of human sexual experience as embodied in the body. The phenomenon of cybersex as a form of digitally mediated sexual activity is commonly adopted by the younger generation under the assumption that the absence of physical contact guarantees the safety of such activities. However, this perception implicitly perpetuates an anthropological reduction that separates the body from the person as a relational subject. This study aims to examine the phenomenon of cybersex through the lens of John Paul II’s Theology of the Body by applying a critical-analytical literature review method encompassing descriptive, evaluative, and synthetic stages. The findings indicate that cybersex represents a significant anthropological-theological crisis in the “Onlife” era, where the blurring of boundaries between physical and digital realities distorts the meaning of the body as a medium of “self-gift.” Within John Paul II’s theological framework, the body is a “personal sacrament” that carries spousal meaning toward authentic relational love. Conversely, cybersex constitutes a distortion that reduces the body to a visual object of consumption, fragmented from genuine personal relationships. This study argues that an adequate pastoral response must go beyond mere normative prohibitions, toward an integrative anthropological approach capable of reclaiming the dignity of the body as the locus of authentic love amidst the complexities of the digital age.